2023
DOI: 10.21203/rs.3.rs-2523386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of Machine Learning Models aiming at Knee Osteoarthritis Diagnosing: an MRI Radiomics Analysis

Abstract: Background To develop and assess the performance of machine learning (ML) models based on magnetic resonance imaging (MRI) radiomics analysis for knee osteoarthritis (KOA) diagnosis. Methods This retrospective study analysed 148 consecutive patients (72 with KOA and 76 without) with available MRI image data, where radiomics features were extracted and then filtered. Intraclass correlation coefficient (ICC) was calculated to quantify the reproducibility of features, and a threshold of 0.8 was set. The trainin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…One study delineated the ROI of the cartilage to construct a model for diagnosing clinical OA. The radiomics feature model performed well in diagnosing clinical OA (AUC, 0.984) (Cui et al, 2023). In addition, a recent study suggested that the texture of the infrapatellar fat pad based on MRI is related to the future development of knee OA and can be used to predict the diagnosis of knee arthritis 1 year later (Ye et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…One study delineated the ROI of the cartilage to construct a model for diagnosing clinical OA. The radiomics feature model performed well in diagnosing clinical OA (AUC, 0.984) (Cui et al, 2023). In addition, a recent study suggested that the texture of the infrapatellar fat pad based on MRI is related to the future development of knee OA and can be used to predict the diagnosis of knee arthritis 1 year later (Ye et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…One study delineated the ROI of the cartilage to construct a model for diagnosing clinical OA. The radiomics feature model performed well in diagnosing clinical OA (AUC, 0.984) (Cui et al, 2023). In addition, a recent study suggested that the texture of the infrapatellar fat pad based on MRI is related to the future development of knee OA and can be used to predict the diagnosis of knee arthritis 1 year later (Ye et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…One study delineated the ROI of the cartilage to construct a model for diagnosing clinical OA. The radiomics feature model performed well in diagnosing clinical OA (AUC, 0.984) (Cui et al, 2023). In addition, a recent study suggested that the texture of the infrapatellar fat pad based on MRI is related to the future development of knee OA and can be used to predict the diagnosis of knee arthritis 1 year later (Ye et al, 2023).…”
Section: Discussionmentioning
confidence: 95%